Macroeconomic effects on Islamic banks performance / Ahmad Zakwan Hafiz Ziad - Ziad, Ahmad Zakwan Hafiz (2015)
This study will focus on the macroeconomic effects on Islamic banks performance. This study was conduct because there are many Islamic financial institution growths and there are also conventional banks that develop and introduce their Islamic financial system. The growth of Islamic banks performance in this short time make more interested for the researcher to start this research. Base on previous study, there are many variables that can be use in the study. The researcher has focus on macroeconomic factors that’s gross domestic product (GDP), interest rate, and inflation rate as the independent variable. Researcher has chosen performance of Islamic Banks as the dependent variable and it is determine by using return on Asset (ROA). Basically the objective of the study is to determine the significance relationship between independent variable and dependent variable. It is also to study the most macroeconomic effects on Islamic banks performance The scope of this study is using penal data by using eleven (11) Islamic banks in Malaysia for five (5) years from 2009 until 2013. The data are collected from Bank Negara Malaysia, World Bank, Bank scope and UiTM database. Data been run using STATA 10.1 software that generate descriptive statistic, Pearson’s correlftion coefficient, pooled ordinary least square (POLS) regression, random effect model (REM) and fixed effect model (FEM). The finding shows that there are positive and significance relationship between GDP and ROA but negative relationship and not significance between interest and inflation rate with ROA. The overall result shows the value of 24.76%, indicates that all the three constructed independent variables were able to explain the relationship with dependents variable profitability on Islamic banks h Malaysia.